Implementing Practical Inventory Control Strategies for Micro-Enterprise Document Reproduction Services - Nurhidayah Nurhidayah; Dwi Rezki Dea Purwasari; Andi Nurul Azisah; Nurul Maghfirah Surianto; Itsna Muflikhah (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Document reproduction services represent an essential segment of micro, small, and medium enterprises (MSMEs), supporting administrative needs across communities and educational environments. However, many micro-enterprises in this sector lack effective inventory control strategies, resulting in risks of stock shortages or excess materials. These issues may disrupt operational continuity, reduce efficiency, and affect service quality. This community service program aims to strengthen the managerial capacity of MSME operators by providing practical education on inventory control strategies through simple planning techniques and structured record-keeping. A descriptive qualitative approach was employed through direct observation, interviews, documentation, and educational material delivery. The findings indicate an improvement in participants’ understanding of inventory planning, efficient ordering decisions, and the importance of maintaining routine stock records. Business owners expressed their commitment to implementing simple inventory logs and preparing priority supply lists as initial steps toward more effective stock management. These results suggest that practical education can serve as a valuable intervention to enhance inventory governance among micro-enterprise document service providers.